HUBUNGAN ANTARA KREATIVITAS DENGAN HASIL BELAJAR FISIKA - Wizahfitri, Puput Amanda; Syamsu (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aims to determine the relationship between creativity and physics learning outcomes. The population in this study were all students of class XI, and the selected sample were 22 students, with sampling based on certain considerations. Collecting data by providing creativity tests in physics and physics learning outcomes tests with previously taught material. The data analysis technique was carried out by descriptive statistical analysis, while to determine the relationship between the two variables, creativity and physics learning outcomes, it was obtained through calculations with product moment correlation. The results showed that there was a positive and significant relationship between creativity in physics and physics learning outcomes for class XI students of SMA Negeri 4 Palu in the 2018/2019 academic year. It was indicated by the Pearson correlation value on SPSS of 0.839 with a large percentage of the contribution of creativity in physics to physics learning outcomes of 70.3%, the magnitude of the relationship between creativity in physics and physics learning outcomes was r = 0.839 and t = 18.303 the value of this category was included in very strong category which indicates a significant relationship between creativity and physics learning outcomes.